Behaviors of welded hollow spherical joints strengthened by unidirectional annular ribs. (April 2021) - Guo, Zhi; Xu, Xiuchen; Du, Yansheng; Chen, Zhihua
Abstract: Welded hollow spherical joints are comprehensively used in spatial steel structures. However, the original joints cannot meet the strength requirements in some conditions, such as the corrosion, the fire and the change of structural load. Therefore, it is necessary to explore effective methods of strengthening the joints to maintain the durability and safety of the structures. This paper proposes and investigates the method of strengthening welded hollow spherical joints using unidirectional annular ribs. Experiments were conducted to study the failure modes, axial load–displacement curves and ultimate bearing capacity under axial compressive and tensile load. Nonlinear finite element (FE) model was established and verified to study the failure mechanism and bearing capacity of the test joints using ABAQUS. Based on the accurate FE model, parametric studies were performed to study the influence of the thickness and height of unidirectional annular rib, the dimensions of the steel tubes and the welded hollow spheres on the capacity of the joints. Practical design formulas were proposed based on the test and the FE analysis. The conclusions presented in this study can provide theoretical and numerical basis for the design of welded hollow spheres strengthened with unidirectional annular ribs in spatial steel structures.